2011
DOI: 10.1038/cdd.2011.52
|View full text |Cite
|
Sign up to set email alerts
|

A novel RING finger protein, Znf179, modulates cell cycle exit and neuronal differentiation of P19 embryonal carcinoma cells

Abstract: Znf179 is a member of the RING finger protein family. During embryogenesis, Znf179 is expressed in a restricted manner in the brain, suggesting a potential role in nervous system development. In this report, we show that the expression of Znf179 is upregulated during P19 cell neuronal differentiation. Inhibition of Znf179 expression by RNA interference significantly attenuated neuronal differentiation of P19 cells and a primary culture of cerebellar granule cells. Using a microarray approach and subsequent fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 44 publications
9
45
0
Order By: Relevance
“…Thus, ChIP experiments showed a similar presence of WT or DNmB protein in the promoters, while DmB or Y152KN428A were absent. Addition of retinoic acid (RA) to P19 cells induces cell cycle arrest (Pao et al, 2011). In agreement with results described in Fig.…”
Section: Deletion Of Motif B Impairs Brd2-mediated Stimulation Of Thesupporting
confidence: 80%
“…Thus, ChIP experiments showed a similar presence of WT or DNmB protein in the promoters, while DmB or Y152KN428A were absent. Addition of retinoic acid (RA) to P19 cells induces cell cycle arrest (Pao et al, 2011). In agreement with results described in Fig.…”
Section: Deletion Of Motif B Impairs Brd2-mediated Stimulation Of Thesupporting
confidence: 80%
“…It has been reported that RA increases the number of G1 phase cells and the expression of p27 in P19 cells (Sasaki et al, 2000;Pao et al, 2011). In this paper, we described that ectopic Prdm12 has the same function in P19 cells and that RA could induce the expression of Prdm12.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, localization of neurolastin to different endocytic vesicles implicates a substantial role in endocytic membrane dynamics. Furthermore, changes in the expression of different endocytic proteins upon shRNA-mediated knockdown of neurolastin have been reported (Pao et al, 2011). Additionally, we find that neurolastin KO mice have smaller endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…It maps within the chromosomal region encoding the Smith-magenis syndrome (Kimura et al, 1997), a developmental disorder and has known homologs only in higher eukaryotes. Though neurolastin has been shown to be brain-specific with a temporal increase in its expression (Orimo et al, 1998; Pao et al, 2011), there is no direct evidence demonstrating its E3 ligase activity and a very limited understanding about the overall function of this protein. Only recently, a few studies have suggested that neurolastin is important for neuronal differentiation and neurogenesis (Lin et al, 2013; Pao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%